Provider burnout and patient-provider communication in the context of hypertension care. Issue 8 (August 2019) - Robbins, Rebecca; Butler, Mark; Schoenthaler, Antoinette
Highlights: Research on provider burnout and communication has yielded mixed results. In our study, high burnout providers demonstrated more suboptimal care and less relationship building compared to low burnout providers. The contribution of provider burnout to patient outcomes needs further research. Abstract: Objective: Burnout is prevalent among healthcare providers and associated with poor patient-provider communication. Patient-provider communication is essential for effective care, particularly among patients with conditions such as hypertension. We examined the association between provider burnout and patient-provider communication in hypertension care. Methods: We used cross-sectional data from 26 primary care providers and their 80 patients with hypertension. Patient-provider primary care visits were audiotaped and providers completed surveys. Patients were 65% Black/African American and 58% female. Providers were 54% white and 65% female. Patient-provider communication was coded using the Medical Interaction Process System (MIPS). We also assess provider-reported level of burnout and suboptimal patient care using validated surveys. Results: Our findings show an inverse association between burnout and relationship building communication (e.g., displaying empathy) (b=-4.7 p < .05) and between relationship building communication and suboptimal patient care (b=-0.6 p < .05) in multivariate, adjusted models. Conclusion: Given the role of patient-provider communication, our work highlights provider burnout as a potentially significant hindrance to patient-provider relationship building in hypertension care. Practice implications: Future research should examine the factors that contribute to provider burnout in order to mitigate their negative effects on patient-provider communication and patient care.